The Content Mastery among Islamic Education Teachers in Junior Islamic Secondary Schools in Surakarta - Munadi, Muhammad (Institut Agama Islam Negeri Imam Bonjol Padang, 2017)
The study aims to describe the content mastery among Islamic Education teachers in all MTs/N (Islamic Secondary School) located in Surakarta. A mixed method was used in this study, where the teachers of MTsN and private MTs in Surakarta involved in this study. Test, interview and documentation became the instruments of this study. For ensuring the validity, the researcher used expert judgment. The data was analyzed by using descriptive statistics. The results of the study showed that in overall the average scores in the Islamic Education materials had been 74 – which was quite low for a teacher. Meanwhile, some of the teachers got only 47 as compared to100 for the maximum score. From four subjects in the Islamic Education, the score of the teachers’ academic test from the highest to the lowest would be displayed as follows: Qur’an Hadits were 76.40; Fiqh was 76.40; SKI was 73.46; and Aqidah Akhlak was 72.40. It Indicated that the content mastery in the Qur’an – Hadits and Aqidah Akhlak had been higher than that of Fiqh and SKI.